China’s Pseudo-monetary Policy - Deng, Yongheng; Morck, Randall; Wu, Jing; Yeung, Bernard (Review of Finance, 2015)
Abstract China’s monetary stimulation after the global financial crisis rapidly boosted its GDP. We argue that its efficacy derives from state control over its banking and corporate sectors. Beijing ordered state-owned banks to lend and they lent. Beijing ordered centrally-controlled state-owned enterprises (SOEs) to invest and they invested. Our data show much of this investment was highly leveraged purchases of real estate and land prices rises occurred where these SOEs were active buyers. This episode mimics the credit channel for monetary policy, but actually entails internal transfers between arms of the government pressuring on real estate prices upwards.